KERJASAMA INDONESIA-JEPANG MELALUI JOINT CREDITING MECHANISM DALAM GREEN SISTER CITY SURABAYA –KITAKYUSHU TAHUN 2013 - Zattil Husni; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the cooperation undertaken by Indonesia - Japan in low carbon development through Joint Crediting Mechanism. This cooperation is realized in the form of inter-city cooperation or green sister city with case study of surabaya city (indonesia) with kitakyushu city (japan). The Japanese provide incentives for funds and technology transfer for low-carbon development in Indonesia, from which the Japanese will get carbon quota from low-carbon development outcomes in Indonesia, while the Indonesians get real results from low-carbon development in the country.In cooperation Joint Crediting Mechanism Indonesia - Japan, in the low-carbon development of 2013, the author use qualitative research methodology with data collection techniques literature study. the perspective used is green thougth. The level of analysis used is the nation-state. The theory used is green political theory according to R. Eckersley.JCM City to City cooperation is implemented in the green sister city by Surabaya and Kitakyushu in four major sectors implemented in the green sister city program: energy sector, solid waste management, industrial waste management and water resources.Keywords: Green Theory, Joint Crediting Mechanism, Kitakyushu